Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acsaem.8b00652
|View full text |Cite
|
Sign up to set email alerts
|

Adding a New Member to the MXene Family: Synthesis, Structure, and Electrocatalytic Activity for the Hydrogen Evolution Reaction of V4C3Tx

Abstract: Two-dimensional transition-metal-based carbides (or nitrides), so-called MXenes, that can be derived from the three-dimensional MAX phases, have attracted considerable attention throughout the past couple of years. The particular structure together with their hydrophilic and metallic nature make them promising candidates for a plethora of applications, such as sensors, electrodes, and catalysts. Obviously, the respective chemical and physical properties are highly dependent on the chemical composition, stoichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
125
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(135 citation statements)
references
References 31 publications
5
125
0
Order By: Relevance
“…This result corresponds to the highest performance ever reported for MXene phase catalysts in acidic media and it can also be compared with previously reported MoS 2 based materials in the literature (Table S1, Supporting Information). As shown in the summary of recent reports in Figure f, very high overvoltage (>−600 mV) is required in case of Ti‐ (Ti 2 CT x and/or Ti 3 C 2 T x ), V‐based MXene catalysts which are not chemically modified, and Mo‐based (Mo 2 CT x and Mo 2 TiC 2 T x ) or its composite material (MoS 2 /Ti 2 CT x ) . However, previous results mentioned so far show that electrocatalytical activation of the most frequently used Ti‐based MXene can easily induce electrochemical activation via chemical modification, likely simple doping or complexing with heteroatoms such as nitrogen (N) …”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…This result corresponds to the highest performance ever reported for MXene phase catalysts in acidic media and it can also be compared with previously reported MoS 2 based materials in the literature (Table S1, Supporting Information). As shown in the summary of recent reports in Figure f, very high overvoltage (>−600 mV) is required in case of Ti‐ (Ti 2 CT x and/or Ti 3 C 2 T x ), V‐based MXene catalysts which are not chemically modified, and Mo‐based (Mo 2 CT x and Mo 2 TiC 2 T x ) or its composite material (MoS 2 /Ti 2 CT x ) . However, previous results mentioned so far show that electrocatalytical activation of the most frequently used Ti‐based MXene can easily induce electrochemical activation via chemical modification, likely simple doping or complexing with heteroatoms such as nitrogen (N) …”
Section: Resultsmentioning
confidence: 94%
“…These suggest that the surface terminal groups (T x = O, OH, and F) play as the major electrocatalytic active sites for the hydrogen evolution. However, only a limited number of MXenes has been experimentally studied (Ti 2 CT x , Ti 3 C 2 T x , Ti 4 N 3 T x , Mo 2 CT x , Mo 2 Ti 2 CT x , and V 4 C 3 T x ) as electrocatalysts for HER, and unlike theoretical calculations, it was shown that the electrocatalytic performances of Ti‐based MXenes (Ti 2 CT x and Ti 3 C 2 T x ) and V 4 C 3 T x are poor (overpotential ( ƞ ) > 600 mV), with a notable exception for Mo‐based MXene (Mo 2 CT x ) . Therefore, many research groups have attempted to improve electrocatalytic properties through modification of the terminal functional groups on the basal plane of MXenes, and as a representative study, the HER performance of Mo 2 CT x is improved through controlling the terminal functional group coverages on the basal planes by using various etchants .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inherited from the MAX phases, the 2D M n+1 X n layers also have hexagonal symmetry and in analogy to graphene, which has hexagonal symmetry, they have been named MXenes. Over [3,27,28,29,30,31,32,33].…”
Section: Crystalline Max Phases and Their 2d Derivative Mxenesmentioning
confidence: 99%
“…Subsequently, a series of different MXenes materials, which possesses various M or/and C or/and n, are synthesized and reported using similar wet chemical etching method, and the naming rules follow the convention described above. For example, Zr 3 C 2 T X , Ti 4 N 3 T X , V 4 C 3 T X , Ta 4 C 3 T X , Ti 2 CT X , V 2 CT X , Nb 4 C 3 T X , Cr 2 CT X (Naguib et al, 2013;Ghidiu et al, 2014b;Urbankowski et al, 2016;Yang et al, 2016;Zhou et al, 2016;Tran et al, 2018;Wu et al, 2018;Xu et al, 2019). In the early stage, MXenes family were roughly classified into the following three categories according to the variable n: M 4 X 3 , M 3 X 2 , and M 2 X (Khazaei et al, 2018).…”
Section: Introductionmentioning
confidence: 99%